Approximated solution of Van der Pol equation describing transition from forced to free mode of oscillation. Issue 13 (1st June 2013) - Jany, C.; Siligaris, A.; Zarudniev, M.; Ferrari, P.
Abstract : A compact expression describing the transient behaviour of the Van der Pol oscillator is presented. An original simplification on the amplitude variation leads to a new expression of the oscillation phase transient behaviour. This new expression is particularly suitable for describing oscillator relaxation, i.e. when the oscillator switches from a forced to a free oscillation state. It is shown that by choosing the injection stop instant correctly, the free running frequency can be achieved instantaneously.